The Effect of CAR, NPL, and ROA on the Share Price of Infobank15 Index Banking Companies Listed on the IDX for the Period 2020 – 2024 - Elvidasari Sijabat; Suci Azzahra; Renny Maisyarah (CV. AFDIFAL MAJU BERKAH, 2025)
This research was conducted on the Infobank15 index banks listed on the IDX with the research objective to determine the effect of CAR, NPL and ROA ratios on banking stock prices on the IDX. The type of data used is secondary data and the data source used is the company's financial statements related to financial ratios. Data collection techniques using literature study and documentation. The data analysis technique is multiple linear regression, classical assumption test, and hypothesis testing. The results showed that the CAR and ROA ratios partially had a positive and significant effect on the share price of the infobank15 index banks listed on the IDX, while the NPL ratio partially had no significant effect on the share price of the infobank15 index banks listed on the IDX. There is a sufficient correlation between CAR, NPL, and ROA with the stock price of banking companies, and banking stock prices can be explained by the CAR, NPL, and ROA ratios of 31.8% and the remaining 68.2% can be explained by other variables not studied.